(untitled) (Центральноазиатский журнал образования и инноваций, 2024)
This article is devoted to the development of human capital in the digital economy, reflecting on the potential and prospects of Uzbekistan in this matter today. The study analyzes the role of human capital in the economic system and the factors of effective organization of its activities, as well as the impact of human capital development in a modern market economy on the development of innovations in companies. At the same time, the article examines the history of the emergence of human capital, the foundations of its formation and development and stops at the stages of its formation.